Effect of cold deformation on corrosion behavior of selective laser melted 316L stainless steel bipolar plates in a simulated environment for proton exchange membrane fuel cells. (June 2022) - Ma, Jiawei; Zhang, Baicheng; Fu, Yu; Hu, Xiaojun; Cao, Xinfeng; Pan, Zhimin; Wei, Ya; Luo, Hong; Li, Xiaogang
Abstract: This work studied the influence of cold deformation on the microstructure evolution and corrosion behavior of selective laser melted (SLMed) 316L stainless steel in a simulated cathode environment for proton exchange membrane fuel cells (PEMFCs). Results indicated that at < 50% deformation levels, the corrosion resistance was improved with an increase in deformation level, which was attributed to the deformation twins, refining sub-grains, and the formation of stable passive films. At 70% deformation level, martensite nucleation decreased the stability of the passive film and consequently reduced the corrosion resistance. Highlights: Cold deformation showed negative and positive effects on the corrosion resistance of SLMed 316L SS. The relationship between the microstructure and corrosion behavior were established. Semiconductor types of the passive film were independent of cold deformation.